The Sound of Silence: Women’s Voices in Medicine and Law - Spruce, Tracey E. (Columbia Journal of Gender and Law, 1998)
Once upon a time, there was a young girl named Angela Stoner. Her friends and family called her Angie. When she was thirteen, she was diagnosed with a rare form of cancer in her left leg and had to undergo radiation and chemotherapy. The treatments made her sick and she lost her hair. The doctors had told her she was going to die; instead she survived. She eventually graduated from high school and took a job as a receptionist. Angie fell in love with Rick Carder when she was twenty. They moved in together a year later. One day, Angie felt a familiar pain in her left leg. She had a feeling the cancer was back and she was right. This time it was called osteogenic sarcoma and had grown into her hip. The doctors amputated her left leg and half of her pelvis. Angie felt sure that this was finally the end of the cancer. She had beat it.